Apple pectin-based Zataria multiflora essential oil (ZEO) nanoemulsion: An approach to enhance ZEO DNA damage induction in breast cancer cells as in vitro and in silico studies reveal - Salehi, Fahimeh; Behboudi, Hossein; Salehi, Elaheh; Ardestani, Sussan K.; Piroozmand, Firoozeh; Kavoosi, Gholamreza (Frontiers in Pharmacology, 2022)
ZEO is a natural complex of compounds with a high apoptotic potential against breast cancer cells and minor toxicity to normal cells, however, similar to many EOs, ZEO utilization in pharmaceutical industries has limitations due to its labile and sensitive ingredients. Nanoemulsification using natural polymers is one approach to overcome this issue. In this study, an Apple Pectin-ZEO nanoemulsion (AP-ZEONE) was prepared and its FTIR spectra and physical properties were characterized. Furthermore, it was shown that AP-ZEONE substantially suppresses the viability of MDA-MB-231, T47D, and MCF-7 breast cancer cells. AP-ZEONE significantly triggers apoptotic morphological variations and DNA fragmentation confirmed by fluorescent staining and Tunnel assay. Moreover, AP-ZEONE induced apoptosis in MDA-MB-231 cells by loss of the mitochondrial membrane potential (ΔΨm), associated with the accumulation of Reactive Oxygen Species (ROS), G2/M cell cycle arrest and DNA strand breakage as flow cytometry, DNA oxidation and comet assay analysis revealed. Spectroscopic and computational studies also confirmed that AP-ZEONE interacts with genomic DNA in a minor groove /partial intercalation binding mode. This study demonstrated the successful inhibitory effect of AP-ZEONE on metastatic breast cancer cells, which may be beneficial in the therapy process.